Air infiltrations and energy demand for residential low energy buildings in warm climates. (December 2019) - Guillén-Lambea, Silvia; Rodríguez-Soria, Beatriz; Marín, José M.
Abstract: European building legislation is establishing increasingly stricter requirements to reduce the energy demand of buildings as a measure to decrease energy use and associated carbon emissions. In order to comply with the new standards, the most impactful parameters are subject to important revisions. Airtightness is revealed as an impacting parameter on air conditioning energy demand for nearly Zero Energy Buildings (nZEB). Currently the Passivhaus standard, taken as a constructive reference for nZEB in Europe, establishes 0.6 ACH as the maximum infiltration at 50 Pa for all new buildings irrespective of the climate zone. Nevertheless, the influence of infiltrations on the energy demand is lower in warm climates. This study estimates the potential heating and cooling energy demand for different levels of infiltration rates in southern Europe. For this purpose, a dwelling equipped with a mechanical ventilation system with a heat exchanger has been simulated in TRNSYS. The calculations have been performed in different cities with different levels of infiltrations. This research provides the information required to set airtightness parameters in residential buildings in southern Europe to satisfy the new requirements for nZEB. Highlights: Proposal of the maximum infiltration rate in warm climates for residential nZEB. The infiltration impact on the air conditioning demand depending on the climate has been obtained. Values for n50 are proposed for residential nZEB in warm climates. Recommended value for correlation factor to convert n50 to naverage for nZEB has been obtained.